PENGGUNAAN DESIGN THHINKING DALAM PENGEMBANGAN PRODUK DISTRO â€œSTART FROM SCRATCHâ€ - Aripradono, Heru Wijayanto; Lim, Daniel (Universitas Sahid, 2023)
Currently, in Indonesia, the fashion industry is growing rapidly, especially in line with technological advances. Apparel industry or fashion owrld is also one of the sectors whose development is being prioritized out of the five manufacturing sectors. Distro clothing is ready-to-wear clothing that is currently growing and popular. This distribution is the fastest growing fast fashion clothing concept that has spread rapidly throughout the world because it is the most purchased item and the price is also cheap. To be able to attract consumers and competitive in the market, innovation is needed in a product or business that must be solved. This research was conducted with the aim of understanding the application of design thinking method in the development of clothing products that will be sold to the market. Apart from that, it also aims to encourage creativity and innovation in the clothing industry, solve problems and create creative solutions, understand consumer needs more deeply, and reduce the risk of failure. This study uses the design thinking method which consists of five stages, namely empathize, define, ideate, prototype, and test. The result of this research is that the application of design thinking can be used as a method for designing or developing a product because it functions to find solutions or assist in solving problems and assist in understanding market movements.